8(x-10)=-92

Simple and best practice solution for 8(x-10)=-92 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x-10)=-92 equation:


Simplifying
8(x + -10) = -92

Reorder the terms:
8(-10 + x) = -92
(-10 * 8 + x * 8) = -92
(-80 + 8x) = -92

Solving
-80 + 8x = -92

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '80' to each side of the equation.
-80 + 80 + 8x = -92 + 80

Combine like terms: -80 + 80 = 0
0 + 8x = -92 + 80
8x = -92 + 80

Combine like terms: -92 + 80 = -12
8x = -12

Divide each side by '8'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| (x-8)+x+(x+x-8)*0.75=70 | | (x^2+x)-(x+2)=0 | | (1,06²²-1)/(1,06²²,065) | | 7/2x=105 | | 2x+3(4+4)=2x+3(4) | | 422/x=9 | | -10x=10-10 | | Tan-1(8/3)=69.4 | | 2(4x-5)=-38 | | x^2+y^2+4x+5=0 | | 10+(x-1)10=200 | | log^3x=17 | | 6(3n-1)=4(n+4) | | 8+5y=8900 | | 15x-1=9-5x | | 3q=11q | | 18x^2+25x-15=0 | | 4(2x-6)=3c | | 73*10+6+-13=723 | | 73*10+6-13=723 | | 4c+4d+2c-8d= | | z+2iz=2i+1 | | 9x-100=3x-10 | | -3-4x=5-6x | | 36/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4=0 | | 3x+9=31-5x | | 36/0.4=1231 | | 36/0.4=0 | | -1-4x=5-6x | | 16-4[9-3(2x-5)]=-4(3-6x) | | 7x*12y=2a*12b | | 3-4x=5-6x |

Equations solver categories